Formulation of Wound Healing Hydrogel from Keratin Protein - Rabiatul Adawiyah, Zaukifli (2012)
Keratin is a natural protein extracted from the chicken feather. In the developed country, the usage of keratin in the personal care products is widely used. The personal care product produced from the keratin protein is conditioning shampoo, anti aging cream, facial cleanser and others. There are some differences between the personal care products already produced by the other developed country because the raw materials to extract the protein is sheep wool while in this research, the extraction of keratin protein is from chicken feathers. Keratin solution, polyvinyl alcohol. Polyvinyl pyrrolidone, glutaraldehyde and ammonium thioglycollate was mixed intimately. The combination of the solution was then cast and hardened through a freezing-thawing process for 1 hour and this process was repeated up to 7 times to obtain a hydrogel. The related test was conducted to test the effectiveness of the wound healing product.